YIELD OF SOYBEAN CULTIVARS AS AFFECTED BY PLANTING DATE UNDER PESHAWAR VALLY CONDITIONS - Khan, A. Z.; Shah, P.; Khalil, S. K.; Ahmad, B. (The Nucleus, 2020)
Soybean cultivars Epps (MG-V) and Williams 82 (MG-111) were planted on four dates from May to August at one month interval at Malakhandher Farm, Agricultural University Peshawar. The two yields were regressed on date of sowing to quantify the effect of date of sowing on soybean cultivars. A steady decrease in yield was observed as sowing was delayed from May Ist onward. The yield in Epps decreased at the rate of 58.6 kgha-1 day-1 from May to August and of Williams 82 decreased at the rate of 163.6 kgha-1 day-1delay in sowing. On the average Epps produced 4227 kgha-1 total dry matter yield, where as Williams 82 produced 3451 kgha-1 respectively. Both cultivars gave maximum biological and seed yields in early planting than delay planting. It can be concluded that the two soybean cultivars can be planted during May to avoid drastic reduction in yields under Peshawar valley conditions.